RANCANG BANGUN MESIN CNC LASER GRAFIR UNTUK PEMBUATAN BIDANG SILINDER DAN DATAR - IRFAN SANTOSA; Mafazi Rifqi; Mouhammad Agus Shidiq (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2022)
The development of technology that is growing rapidly at this time has had an impact in various fields, including in the industrial sector. In Indonesia, industrial equipment is still mostly imported from abroad. This of course makes it difficult for the industry in Indonesia to develop because of the high price of industrial equipment. To overcome this, it is necessary to conduct research on the design of industrial equipment for domestic production. In this article, a CNC tool is designed that can be used for engraving or in other terms to automatically draw a pattern on a certain area. Laser Engraving Machines require a circuit control system that functions as the brain of the machine. The purpose of this research is to design a control system for a laser engraving machine using a microcontroller. In this study, the method used is an experimental method in the form of a laser engraving machine design including a driving mechanism, structural elements and the design process. All parameters will be set and operated through the CNC control system so that the laser engraving machine can operate properly. The design planning of this CNC Laser Engraving machine has dimensions with a length of 600 mm, a width of 500 mm. The assembly process for the CNC Laser Engraving Machine is classified into several parts, namely: Basic Machine Framework with an assembly time of 50 minutes, Y-Axis Assembly Moves Tool Front-To-Back with an assembly time of 32 minutes, X-Axis Assembly Moves Tool Side-To-Side with assembly time of 13 minutes, Rotary Table with assembly time of 25 minutes. The performance results of each Axis on this CNC Laser Engraving machine have a high level of accuracy, namely: X Axis = 100%, Y Axis = 100%, Rotary Axis = 100%